Does The Pandemic Have an Impact on Consumer Behavior in Malaysia? - Khor, Xin Yun; Kh'ng, Hong Liang; Maran, Kirthiga A/P; Khairunnisa, Khairunnisa; Qureshi, Faika (AIBPM Publisher, 2023)
Due to travel restrictions and social distancing, people migrate to online platforms. The Covid-19 pandemic has prompted Malaysians to shop online instead of going to the store daily. This study investigates how Covid-19 affects customer behavior in Malaysia, where some indicators reveal a shift to online shopping during the pandemic. This study employed a survey research design. We tested hypotheses using SPSS. A total of 200 respondents participated in this survey. The data were analyzed with descriptive statistics and inferential statistics. The finding revealed that price, convenience, and service quality could directly affect customer behavioral intention. We also found that online trustworthiness and perceived trust can impact customer satisfaction. Recommendations for the retail industry in Malaysia to sustain its business model for the future are presented.Keywords: Consumer behavior, Retail industry, Online shopping, Malaysia, Covid-19 Pandemic